What makes them so good - The constructs used by coaches to identify coaching prowess - Stoszkowski, J.; Collins, D. (Athletic Insight Journal, 2015)
The criteria used by coaches to judge their peers are extremely pertinent to the study and enhancement of coach development. The aim of this two-part study was to offer insight into how a sample of British sub-elite coaches judged coaching prowess and perceived the nature of the expertise possessed (or perceived to be possessed) by their own self-selected role model coaches. Data from field notes and transcribed conversations with 143 coaches, drawn from over 15 years of conversations, were interpreted following an inductive analysis. Subsequently, follow up focus group interviews involving 15 level three coaches in a range of sports were used to augment and, if appropriate, question these data. Results yielded an array of personal characteristics, which participants used to describe "what" role model coaches did or were like, as opposed to professional or behavioural characteristics that explained "how" they worked. Consideration of these findings offers some areas for immediate exploitation, alongside some key concerns which must be addressed if the trend for social learning based coach development initiatives are to have optimum benefit.